THE ANALYSES OF CLOZE PROCEDURE APPLICATION IN TEACHING READING TO THE ELECTRICAL ENGINEERING STUDENTS SEMESTER II STATE POLYTECHNIC OF SRIWIJAYA - Sri Endah Kusmartini (HOLISTICS, 2009)
The study investigates the application of cloze procedure in teaching reading. The purposes of the study is to compare the reading comprehensibility of the students of Electrical Engineering Study Program Electro Department State Polytechnic of Sriwijaya semester two before and after the application of cloze procedure in teaching reading. The population is all students of Electrical Engineering Study Program Electro Department State Polytechnic of Sriwijaya semester two  on the academic year of 2008/2009. The samples are 89 students. The study used descriptive method. To find out the differences, the writer uses cloze test as a measuring tool before the application and after the application. The results show that the reading comprehensibility of the students relatively increases. Before  the application, the  average score of the students is 65.78, and after the application, the average score of the students is 71.92. It means  that there is an increase of 9.40%. The range of the score of the students before the application of cloze procedure is from 50 to 85. And the range of the score of the students after the application of cloze procedure is from 52 to 95. It is hoped that this study will be useful for the teachers to vary their strategies in teaching reading, and the English teaching authorities to develop the English teaching in general.